Equilibrium Exchange Rates : Assessment Methodologies - Isard, Peter (IMF Working Papers; Working Paper ;, 2007)
The paper describes six different methodologies that have been used to assess the equilibrium values of exchange rates and discusses their limitations. It applies several of the approaches to data for the United States as of 2006, illustrates that different approaches sometimes provide substantially different assessments, and asks which methodologies deserve the most weight in such situations. It argues that while it is generally desirable to consider the implications of several different approaches, since different approaches provide different types of perspectives, two of the methodologies seem particularly relevant for identifying threats to macroeconomic stability and growth.